THE USE OF BLACK SOYBEAN (Glycine max L) EXTRACT AGAINST THE ACTIVITY OF LIVER ENZYMES (AST - ALT) AND ANTIOXIDANT SUPEROXIDE DISMUSTASE (SOD) OF WHITE RAT - I Gusti Ayu Nyoman Danuyanti; Ersandhi Resnhaleksmana (Jurnal Kesehatan Prima, 2018)
Abstract: Strenuous physical activity can increase the activity of enzymes AST (aspartate aminotransaminase) and ALT (alanine aminotransaminase) in the blood as a sign of hepatic dysfunction caused by oxidative stress as a result. Excessive free radicals that damage macromolecules in cells. The supplementation of black soybean (Glycine max L) contains anthocyanin as an antioxidant is expected to reduce the formation of free radicals thus the activity of liver enzymes and the levels of SOD enzymes as intracellular antioxidant can be maintained. The purpose of this study was to determine the effect of using extracts of black soybean (Glycine max L) on the activity of liver enzymes (AST-ALT) and the antioxidant superoxide dismutase (SOD) of white rats that were given a maximum of physical activity. The research was control group post test design in vivo that used black soya extract treatment given to white rats (Rattus norvegicus) Wistar strain given maximum physical activity. The results indicated black soybean extract 40% was the most powerful retaining the activity of liver enzymes and blood levels of antioxidants SOD. The conclusion is there is an effect of black soybean extract against the activity of liver enzymes (AST-ALT) in rats given maximal activity, whereas SOD enzymes can inhibit the decline of SOD enzyme level to 37.8% but statistically there is no significant influence.Keywords: AST-ALT enzymes; antioxidants SOD; Soybean black; Physical activity maximum.